Applying the principle of justice in digital health - Oriol Yuguero; Pere Ruiz-Trujillo; Montse Esquerda; Nuria Terribas; Marta Aymerich (npj Digital Medicine)
Abstract In an increasingly digital healthcare landscape, it is essential to assess the ethical impact of technology on care practices. We present a conceptual framework on equity in digital health, addressing justice-related concepts and challenges to reducing the digital divide. An ethical approach ensures that digital health respects fundamental rights. We propose goals—such as incorporating digital determinants into public health policy—to promote justice and reduce health inequalities in digital health implementation.